Defluorination Capability of l‐2‐Haloacid Dehalogenases in the HAD‐Like Hydrolase Superfamily Correlates with Active Site Compactness. (22nd October 2021) - Chan, Peter W. Y.; Chakrabarti, Nilmadhab; Ing, Chris; Halgas, Ondrej; To, Terence K. W.; Wälti, Marielle; Petit, Alain‐Pierre; Tran, Christopher; Savchenko, Alexei; Yakunin, Alexander F.; Edwards, Elizabeth A.; Pomès, Régis; et al.
Abstract: l ‐2‐Haloacid dehalogenases, industrially and environmentally important enzymes that catalyse cleavage of the carbon‐halogen bond in S ‐2‐halocarboxylic acids, were known to hydrolyse chlorinated, brominated and iodinated substrates but no activity towards fluorinated compounds had been reported. A screen for novel dehalogenase activities revealed four l ‐2‐haloacid dehalogenases capable of defluorination. We now report crystal structures for two of these enzymes, Bpro0530 and Rha0230, as well as for the related proteins PA0810 and RSc1362, which hydrolyse chloroacetate but not fluoroacetate, all at ∼2.2 Å resolution. Overall structure and active sites of these enzymes are highly similar. In molecular dynamics (MD) calculations, only the defluorinating enzymes sample more compact conformations, which in turn allow more effective interactions with the small fluorine atom. Structural constraints, based on X‐ray structures and MD calculations, correctly predict the defluorination activity of the homologous enzyme ST2570. Abstract : You have to come close if you want a reaction : Several members of the haloacid dehalogenase‐like hydrolases superfamily were found to break carbon‐fluorine bonds. The only features that differentiate between them and other family members unable to achieve this feat were small changes in distance between selected active site residues and protein dynamics leading to tighter interactions between protein and halogen.